Identification of Phosphorylated Proteins Regulated by SDF2L1 in Nasopharyngeal Carcinoma Cells. (April 2022) - Luo, Chengchang; Zhang, Zunni; Su, Qisheng; Mo, Wuning
SDF2L1 is a new type of endoplasmic reticulum stress inducible protein, which is related to poor prognosis of various cancer, we initially studied the low expression level of SDF2L1 in NPC, but the molecular mechanism of SDF2L1 in NPC needs further elucidation. To identify phosphorylated proteins regulated by SDF2L1 in nasopharyngeal carcinoma (NPC), Label-free Quantitative (LFQ) Proteomics and 2D-LC-MS/MS analysis were performed on high metastatic NPC 5-8F cells with overexpression of SDF2L1 and empty segment. Western blotting was applied to validate the differentially expressed phosphorylated proteins (DEPPs). As a result, 331 DEPPs were identified by proteomics, and PARVA phosphorylation (ser8) was validated. The present results suggested that PARVA phosphorylation may be a new promising biomarker for predicting NPC and play a key role in the occurrence and development of NPC.